+0  
 
0
41
1
avatar

https://vle.mathswatch.co.uk/images/questions/question2214.png

 Mar 13, 2021
 #1
avatar+118069 
+1

f(x)  = x/2  +  1               g(x)  =  3x + 2

 

a)  f(1)  + g(2)   =  

 

1/2 + 1  +  3 (2) + 2  =

 

9 + 1/2   =    19 / 2

 

 

b )  We  can solve  this

 

3x + 2  =  11

 

3x  = 9

 

x = 3   =    g-1 (11)

 

In other words  (3,11)  is on g(x)   so  (11 , 3)  is on g-1 (x)

 

 

c) We already know g-1(11)

 

So   we  can solve  this

 

x/2  +  1  =  3

 

x/2   =  2

 

x =  4   =  f-1(3)

 

So     g-1(11)  - f-1(3)   =   3  - 4    =    -1

 

 

cool cool cool

 Mar 13, 2021

31 Online Users

avatar
avatar
avatar
avatar